2015
DOI: 10.18656/jee.86698
|View full text |Cite
|
Sign up to set email alerts
|

Career Decisions of Gifted Students in Turkey

Abstract: The aim of the present study was to examine career decision of gifted students. Participants were consisted of 63 gifted middle school students, fifth through eighth grades, attending a gifted education class within a school. Their ages ranged from 11 to 15. The data was obtained through a survey including questions about demographic information and two open-ended questions about career decisions. The participants' responses were analyzed with content analysis. The results indicated that the most preferred occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
9
0
2
Order By: Relevance
“…Although gifted students generally show real interests, there are wide differences between them. According to Ogurlu [17] found that males have a higher vocational aspiration, prestige, academic achievement, and commit themselves to careers that require physical effort. However, females' express of interests in a wide range of professions that contribute to the attitudes of both the sexes; they want more prestige and tend to exhibit high levels of personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Although gifted students generally show real interests, there are wide differences between them. According to Ogurlu [17] found that males have a higher vocational aspiration, prestige, academic achievement, and commit themselves to careers that require physical effort. However, females' express of interests in a wide range of professions that contribute to the attitudes of both the sexes; they want more prestige and tend to exhibit high levels of personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Συνολικά, τα αποτελέσματα με βάση τον κώδικα επαγγελματικών ενδιαφερόντων του Holland έδειξαν ότι οι χαρισματικοί μαθητές έχουν ποικίλα επαγγελματικά ενδιαφέροντα και δεν ξεχωρίζουν ή κλείνουν προς μία μόνο ομάδα ενδιαφερόντων. Τα αποτελέσματα αυτά συνάδουν και με τα ευρήματα άλλων μελετών που αναδεικνύουν τα πολλαπλά ενδιαφέροντα των χαρισματικών μαθητών σε άλλες χώρες (Stewart, 1999· Cheng, 2011· Kass & Cavallaro, 2010· Sajjad, Muhammad, Khurram & Syeda, 2012· Ogurlua, Kayab & Hizlic, 2015.…”
Section: συμπεράσματαunclassified
“…Additionally, compatibility between personality and environment not only can predict individual's level of satisfaction in life but also contribute towards stability, achievement as well as motivation related to career or education (Holland, 1997). In relation to that, many researches showed a significant relationship between personality and career choices among students including the Gifted and Talented students (GTS) (Cheng, 2011;Kass & Cavallaro, 2010;Ogurlua, Kayab & Hizlic, 2015;Sajjad, Muhammad, Khurram & Syeda, 2012;Stewart, 1999;Watters, 2010). As such, career choices and planning must be carried out meticulously, systematically, and consciously for the results will affect individual's satisfaction and lifestyle in their future career life.…”
Section: Self-knowledge On Personalitymentioning
confidence: 99%